2013
DOI: 10.1016/j.cortex.2013.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Aphasia rehabilitation: Does generalisation from anomia therapy occur and is it predictable? A case series study

Abstract: A cueing hierarchy can improve word retrieval/production for adults with aphasia. In some cases generalisation to untreated items also occurs. The study demonstrates that the results of behavioural testing can be used to guide predictions of recovery with intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 44 publications
3
53
1
Order By: Relevance
“…In a review of 12 the anomia therapy literature, Best et al (2013) found that treatments with a focus on 13 strategy, particularly those that incorporated semantics, were more likely to achieve 14 generalization than treatments that targeted specific representations. If the application of 15 strategy is responsible for generalization, it is hypothesized that executive function would 16 significantly correlate with gains for untreated items.…”
Section: Untreated Itemsmentioning
confidence: 99%
“…In a review of 12 the anomia therapy literature, Best et al (2013) found that treatments with a focus on 13 strategy, particularly those that incorporated semantics, were more likely to achieve 14 generalization than treatments that targeted specific representations. If the application of 15 strategy is responsible for generalization, it is hypothesized that executive function would 16 significantly correlate with gains for untreated items.…”
Section: Untreated Itemsmentioning
confidence: 99%
“…Consequently, the finding of generalisation to untreated items for only a small subset of participants in the present study (post therapy 29%, follow-up 22%) is consistent with previous reports in the literature (Best et al, 2013). Nickels (2002c) and Best et al (2013) suggest that treatments that aim to strengthen connections between word meaning and form often result in clear, long-lasting effects for treated items;…”
Section: Outcomes For Treated and Untreated Itemssupporting
confidence: 80%
“…These treatments provide a structured process to facilitate retrieval of treated items, which can then also be applied to the retrieval of untreated items. Furthermore, Best et al (2013) found that individuals with relatively preserved lexical-semantic processing and more impaired phonological encoding deficits were more likely to demonstrate generalisation to untreated items. In the present study, we found improved naming for untreated items in a small sample of participants.…”
Section: Generalisation Of Treatment Effectsmentioning
confidence: 99%
See 2 more Smart Citations